How to 'downsize' a complex society: an agent-based modelling approach to assess the resilience of Indus Civilisation settlements to past climate change. (21st October 2020) - Angourakis, Andreas; Bates, Jennifer; Baudouin, Jean-Philippe; Giesche, Alena; Ustunkaya, M Cemre; Wright, Nathan; Singh, Ravindra N; Petrie, Cameron A
Abstract: The development, floruit and decline of the urban phase of the Indus Civilisation (c.2600/2500-1900 BC) provide an ideal opportunity to investigate social resilience and transformation in relation to a variable climate. The Indus Civilisation extended over most of the Indus River Basin, which includes a mix of diverse environments conditioned, among other factors, by partially overlapping patterns of winter and summer precipitation. These patterns likely changed towards the end of the urban phase (4.2 ka BP event), increasing aridity. The impact of this change appears to have varied at different cities and between urban and rural contexts. We present a simulation approach using agent-based modelling to address the potential diversity of agricultural strategies adopted by Indus settlements in different socio-ecological scenarios in Haryana, NW India. This is an ongoing initiative that consists of creating a modular model, Indus Village, that assesses the implications of trends in cropping strategies for the sustainability of settlements and the resilience of such strategies under different regimes of precipitation. The model aims to simulate rural settlements structured into farming households, with sub-models representing weather and land systems, food economy, demography, and land use. This model building is being carried out as part of the multi-disciplinary TwoRains project. It brings together research on material culture, settlement distribution, food production and consumption, vegetation and paleoenvironmental conditions.